The Impact of the Job Creation Law's Implementation on Business Legality Compliance and MSME Resilience: Dampak Implementasi Undang-Undang Cipta Kerja terhadap Pemenuhan Legalitas Usaha dan Resiliensi UMKM - Ulya, Widadatul; Afifah, Hana (Lex Renaissance, 2026)
Law Number 6 of 2023 concerning Job Creation plays a pivotal role in promoting the development of micro, small, and medium enterprises (MSMEs) through simplified licensing and business facilitation schemes. Despite these regulatory reforms, the implementation process continues to encounter significant challenges, particularly in ensuring MSME compliance with business legality requirements. In Central Java, a substantial number of MSMEs remain non-compliant due to limited legal literacy and low awareness among business actors. Such conditions undermine MSME resilience due to national economic fluctuations and external shocks, including the COVID-19 pandemic. This study investigates the impact of the Job Creation Law on the fulfillment of business legality requirements and its implications for MSME resilience in Central Java. Employing a qualitative normative-empirical approach, this research integrates primary data obtained through observations and interviews with secondary data derived from legal documents and supporting literature. The findings indicate that the implementation of the Job Creation Law has contributed to a measurable improvement in MSME legal compliance. A policy implementation strategy involving collaboration between MSME Facilitators and Halal Product Processing (PPH) Facilitators has proven effective in improving legal literacy and encouraging business legality management. Strengthened business legality compliance further contributes to MSME resilience by fostering legal certainty, minimizing legal risks, and reinforcing the institutional MSME ecosystem. Consequently, the implementation of the Job Creation Law demonstrates a direct and positive influence on the sustainability and resilience of MSMEs in the region.